Translation, cultural adaptation and validation of the Somatic Symptom Scale-8 (SSS-8) for the Brazilian Portuguese language - Pollo, Camila Fernandes [UNESP]; Meneguin, Silmara [UNESP]; Miot, Hélio Amante [UNESP]; de Oliveira, César (Springer Nature, 2022)
Background: Assessment tools are commonly used in different fields of health to assist in the diagnosis, the evaluation of the response to treatment, the measurement of quality of life and the establishment of the prognosis. Objectives: Translate, culturally adapt and perform the psychometric validation of the Somatic Symptom Scale (SSS-8) for use in the Brazilian population. Methods: Cross-cultural adaptation followed a combination of guidelines and for psychometric evaluation a sample of 300 patients was recruited. All recommended measurement properties by the Consensus-based Standards for the selection of health status Measurement Instruments were evaluated, including analysis by an expert committee and analysis by the target public. The Skindex-16 was used for the evaluation of convergent validity and Cronbach’s alpha was used for the determination of the internal consistency of the translated version of the SSS-8. Results: The final version received approval from five experts and the agreement index was 100% for all items. During the pretest, the scale was administered to 300 patients with psoriasis and none of the items needed to be altered. A moderate correlation was found between the Skindex-16 and SSS-8-BRA. In the analysis of internal consistency, Cronbach’s alpha for the SSS-8-BRA was 0.81. Conclusion: The SSS-8 is a valid and reliable tool for the assessment of somatic symptoms in the Brazilian population.
Keywords: Dermatology; Psychometry; Quality of life; Questionnaires; Somatic symptoms